Conhecimento popular e o uso de plantas medicinais: narrativas de idosos moradores do bairro da Primavera, em Cametá - PA - SILVA, Débora Reis da (2024)
The present study aims to understand, from the selected group of elderly people, how the use of medicinal plants is correlated with popular knowledge and with the history of formation of Bairro Primavera, in Cametá-Pará. The research is anchored in the studies of: Gama (2006), Loya et al (2009), Monteiro and Bradelli (20017), among others that allow us to understand that the use of medicinal plants is an ancient practice, passed on older generations and is strongly linked to popular knowledge. In turn, the empirical data were built through a qualitative research based on the theoretical assumptions of Oral History, carried out with 06 (six) residents of the Neighborhood in question. From the narratives of the interviewees, it is contextualized that Bairro Primavera has a history of construction linked to the use of medicinal plants and this is based on the knowledge of the elderly with whom we dialogued, in the same way, it is considered that when remembering the use of medicinal plants today, the elderly interact with their collective memories shared with others with whom they coexisted and still reverberate popular knowledge that will permeate future generations.